Carex phyllostachys (Cyperaceae), a new species in Croatia - Terlević, Ana (Array, 2020)
The occurrence of Carex phyllostachys (Cyperaceae) in the Croatian flora is documented here for the first time. This rare Euro-Caucasian species was found in June 2019 in deciduous sub-Mediterranean Quercus pubescens-Carpinus orientalis forests on Mt Mosor in central Dalmatia. This record represents the north-western distribution limit of this species. The habitat and ecology of C. phyllostachys in the Croatian flora is presented, and morphological similarities with allied species (C. distachya and C. illegitima) are discussed. An identification key for Carex species belonging to the subgenus Indocarex in Croatia is provided.